A systematic review on self-management education campaigns for back pain - Loveness A. Nkhata; Yolandi Brink; Dawn Ernstzen; Quinnette A. Louw (AOSIS, 2019)
Background: Evidence-based clinical practice guidelines on back pain recommend early management and use of approaches that emphasise self-management, psychological and physical therapies. Lately, mass media campaigns, addressing misconceptions about back pain, have been conducted in developed countries. Objectives: This study retrieved and synthesised the contents of back pain messages and described the outcomes and effectiveness of the media campaigns. Method: Seventeen key words and 10 electronic databases were used to conduct a search between February and July 2018. Authors screened titles, abstracts and full-text articles independently to identify eligible studies. Data were reported using narratives because of heterogeneity in the outcomes. Results: Appraisal of articles was done using the Physiotherapy Evidence Database scale for randomised controlled trials (RCT) (one) or the Joanna Briggs Institute checklist for non-RCT (four). The campaigns were conducted in the general population in Australia, Canada, Norway, the Netherlands and Scotland. The message 'stay as active as possible' increased participants' awareness and influenced their health beliefs and healthcare utilisation behaviours resulting in reductions in sick leave days, work disability, healthcare utilisation and claims. Conclusion: The back pain campaign message 'stay as active as possible' increased participants' awareness and influenced their health beliefs and healthcare utilisation behaviours. Even though the campaigns were done in high-income countries, their contents and methods are transferable to developing countries. However, their implementation must be tailored and efficient and cost-effective methods need to be explored. Clinical implications: Providing information on back pain can contribute to significant changes in sickness behaviours and beliefs.